Analysis of Islamic Business Ethics: Case Study of AL-Mubarak Grocery Store in Blega District - Andini Maulidya; Abdur Rohman (Penerbit Hellow Pustaka, 2025)
This research aims to determine the application of Islamic Business Ethics to basic food traders in Blega Village, Bangkalan Regency. The research method used in this research is an interactive qualitative method. The research results show that the understanding of basic food traders in Blega Village regarding Islamic Business Ethics is not optimal. The majority of basic food traders in Blega Village have implemented Islamic Business Ethics well, and the impact of implementing Islamic Business Ethics on the income of basic food traders in Blega Village is directly proportional.